STATED OWNED COMPANIES OF TIC SYNERGY STRATEGY ANALYSIS: The Origin Problems in Creating Synergies at The Initial Period of Holding - V. Prio Mudo Purwanto; Susilo Toto Rahardjo (Jurnal Akuntansi dan Pajak, 2023)
This study discusses the causes of problems that arise in the creation of a synergy of State Owned Company or BUMN (Badan Usaha Milik Negara) Survey Services in the early stages of restructuring into a holding form. Survey Service Company is another name for TIC Company (Testing, Inspection and Certification). An analysis of the management of creating synergy through a mechanism approach of mutually beneficial cooperation between companies through their business units or at the operational level. This research was conducted on a holding company that was newly formed in December 2021 or at the beginning of the change into a holding form. Respondents gave responses or approvals on fifteen statements that had been designed which were then analyzed for their potential as barriers to the creation of a synergy strategy in the holding of State Owned Company (BUMN) Survey Services. The analysis was carried out on three national survey services companies, using survey data conducted in June 2022 and data for the period 2021-2022 originating from internally the three State Owned Company (BUMN) survey services. Theories and concepts used in this research are strategy, organization, stakeholder and agency theory. This research focuses on the root cause of the problem of creating synergy as an initial research and this first stage will be followed by a second stage of research that will use the results of the research in the first stage. In the first stage of this research, the results showed that in the early stages of the holding the form of the synergy creation strategy that was applied was not able to satisfy the holding members and showed that the holding members were not convinced that the synergy management carried out could benefit each member. This research provides a rationale for the management of creating synergies that are implemented in the holding of the State Owned Company (BUMN) Survey Services and generating opportunities for strategic actions towards the creation of better synergies. Research is useful for scientific development in the field of strategic management and for further research. Keywords: Creating Synergy, Barrier to creating synergy, Synergy Strategy, Holding, Opportunities for Startegic Actions, Shared Resource.